Effect of Selected Procurement Systems on Building Project Performance in Nigeria - Oladirin, Olugbenga Timothy; Olatunji, Samuel Olusola; Hamza, Basir Tomiwa (International Journal of Sustainable Construction Engineering and Technology, 2013)
Every client at the beginning of any project aims at having value for the money spent via a quality structure delivered on time and within budget by the contractor. However, researches have shown that in most cases this aim is not met. Therefore, this study examines the effect of procurement systems on building project performance in Nigeria, with a view to assess their effect on cost and quality. The data for this study were collected with the aid of structured questionnaires which were administered to actors in the construction industry in Lagos state being the major hub of construction activities in Nigeria. The questionnaires were related to the variants of procurement systems common to the Nigerian construction industry. Data analysis was done using descriptive statistics. The result revealed that the traditional system of procurement is the most adopted option in project execution in Nigeria. Meanwhile, design and build system performs better in cost, but lag construction management system in quality achievement. The study concluded that no procurement system is a do it all in that a procurement system may perform better than the other in an instant and fail in others as revealed in the findings. The study finally recommends that consultants and other stakeholders in the construction industry and particularly those in the building sector should be up to date as to be able to suitably advise clients when it comes to building procurement, and that before choosing a procurement system the main objective and even supporting objectives should be established